Pengaruh Sistem Pembayaran Elektronik Terhadap Permintaan Uang Di Indonesia Dalam Perspektif Ekonomi Islam - duwi puspita; Ary Dea Amry; Dea Anjelinah; Ananda Wahitora; Asraf Mustafa (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
Along with the development of technology and information, the payment system used as a medium of exchange in economic activities continues to change. Current economic transactions do not only use cash but also use electronic non-cash instruments which are more efficient and economical. The purpose of this study was to determine the effect of APMK (debit cards, credit cards) and electronic money on the amount of money demanded. This study uses secondary data sourced from Bank Indonesia and the Central Bureau of Statistics. The data used is annual time series data from 2018 to 2022. The analysis technique used in this study uses multiple linear regression analysis techniques. The results obtained in this study indicate that transactions using debit cards, credit cards and electronic money simultaneously have a significant effect on the amount of money demanded. Viewed partially, debit cards, credit cards and electronic money do not have a significant effect on the amount of money demanded .